Perancangan Digester Biogas dari Kotoran Sapi dan Limbah Cair Tahu dengan Sistem Sirkulasi - Oktria, Dandi; ., Rosalina; Supriadi, Eko (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
Biogas is renewable energy consisting of 55-65% methane, 35-55% carbon dioxide, and 0.1-3% hydrogen sulfide. advantage of biogas lies in its abundant availability. Biogas is produced anaerobically using organic raw materials mediated by microbes. The biogas production process consists of four stages, namely hydrolysis, acetogenesis, and methanogenesis. supporting materials used are 150 liters and 55 liters HDPE drums, ½ in the pipe, ¾ in the pipe, ½ in T the pipe connection, ½ in the pipe elbow, ½ in the pipe valve, ¾ in thread socket, 1 bar pressure gauge, 1 bimetal thermometer required, water pump. The tools used include pH meters and gas detectors. CSTR-type digester uses a pump as the circulation system. The advantages of using a circulation pump are maintaining operating temperature, increasing material contact, inhibiting sedimentation, and reducing fermentation time. In the design of the Digester tool, a gal holder is also used as a container for the biogas produced by the Digester during operation, the result of variations in circulation which are carried out every 4 days, and the addition of raw materials every day is 3 liters/day, 1.5 liters of cow dung and 1.5 liters of tofu liquid waste resulted in variation 0 circulations 41% methane, pressure 0.1, COD value 13,200, variation 30 circulations 52% methane, pressure 0.16, COD value 11,792, variation 60 circulations 55% methane, pressure 0 .18, and a COD value of 10,560, and at variation 90 circulations 58% methane is produced, a pressure of 0.19, and a COD value of 7,040.